Payback time : making big money is the best revenge! - Town, Phil (New York : Crown Business, 2010)
From the bestselling author of'Rule #1' comes a perfectly timed book that shows why a beaten-down market represents the best opportunity to get rich, and it teaches readers how to finally beat the system that failed them
Keywords: Investments; Investment analysis; Finance, Personal